Coach of the year (Digiview Productions, 2004)
Jim Brandon, a Vietnam War veteran and former Chicago Bears player who is now confined to life in a wheelchair. Embittered by his situation, Brandon begins feeling desperate to regain a part in the athletic world. After many job rejections, he is finally offered a job coaching a football team at St. Charles, the local juvenile detention center. Though initially there id discord between Jim Brandon and the children, they gradually come to see each other in a different light. Together thy embark on a journey and respect that eventually culminates in a climatic showdown with a powerful high school team.